The Role of Promotion in Increasing Sales of Red Coffee Cap Lesung SMEs New Hope Built at BDC Pagar Alam City - Dewi, Dismita Citra (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The primary purpose of this study is to determine the promotion strategy to increase coffee sales at Cap Lesung Ukm Harapan Baru Binaan BDC Kota Pagar Alam. To achieve the research objectives, researchers made observations at UKM Harapan Baru Binaan BDC to collect data on the material studied. The results obtained using descriptive analysis are as follows: 1) Marketing of SMEs Harapan Baru Binaan BDC Kota Pagar Alam using marketing mix variables from advertising, personal selling, and sales promotion to diluted red coffee products cap lesung; 2) UKM Harapan Baru Binaan BDC Kota Pagar Alam promotes through these media, namely radio, Facebook, Instagram, Shoppe, website, and sponsorship (event); 3) From the discussion analysis, it is known that the increase in promotional costs every month causes an increase in sales volume, which shows the relationship between promotional costs and sales volume, where each change in promotion variables affects sales volume; 4) From the results of the study, the most dominant factor of the role of promotion to increase sales is advertising. The ads used are based on social media, namely the internet, Facebook, Instagram, and Shoopee, which experienced profits from sales of Rp. 20,000.00 in 2021, then experienced an increase of Rp. 25,000.00 (by 1.15%), and Rp. 29,500,000 (by 1.18%) in 2023